2016
DOI: 10.1021/acs.jpcc.6b04468
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Trap-State-Mediated Exciton Transport in Perovskite-Shelled PbS Quantum Dot Thin Films Using Photocarrier Diffusion-Wave Nondestructive Evaluation and Imaging

Abstract: Perovskite-shelled colloidal quantum dots (CQDs) with low trap-state density are promising candidates for largescale, low-cost, and lightweight solar cell applications. However, even minimal trap states can significantly limit CQD-based solar cell efficiency. We reported trap-state-mediated exciton transports in methylammonium lead triiodide (MAPbI 3 ) perovskitepassivated PbS CQD thin films. Excitation power-dependent photocarrier radiometry (PCR) intensity study demonstrated the free (electrons/holes)-to-bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 72 publications
2
15
0
Order By: Relevance
“…The TA spectra of the MAPbI3/QDs and Consequently, the blue shift in the PB2 band of MAPbI3/QDs is due to changes in the electronic and/or crystallographic structure of MAPbI3 in presence of the QDs. Such modifications were observed after passivation by the QDs due to the lattice mismatch between the two materials [18,21,44,45]. The interpretation of the blue shift also agrees with reported band gap expansion of MAPbI3 related to structural deformation [46].…”
Section: Transient Spectra and Decayssupporting
confidence: 87%
See 1 more Smart Citation
“…The TA spectra of the MAPbI3/QDs and Consequently, the blue shift in the PB2 band of MAPbI3/QDs is due to changes in the electronic and/or crystallographic structure of MAPbI3 in presence of the QDs. Such modifications were observed after passivation by the QDs due to the lattice mismatch between the two materials [18,21,44,45]. The interpretation of the blue shift also agrees with reported band gap expansion of MAPbI3 related to structural deformation [46].…”
Section: Transient Spectra and Decayssupporting
confidence: 87%
“…Thirdly, electrons can be transferred and subsequently trapped in perovskite/QDs interface. Indeed, it has been reported that, in the presence of QDs, the crystallographic structure of the MAPbI3 lattice might be different inside the crystallite and at the interface with the QDs, thus, new trap states will appear [18,21,44].…”
Section: Description Of the Modelmentioning
confidence: 99%
“…A better electrode coating with lower interface states leads to low S ( d ) that results in higher CQDSC performance. To investigate the CQD/Au interface effects on CQDSC performance, nondestructive imaging (NDI) of carrier population distributions and key photovoltaic parameters was conducted using LIC, a spectrally gated dynamic frequency‐domain photoluminescence‐based transport property imaging method . The LIC images revealed the complexity and inhomogeneity of the electrode‐coating‐associated surface recombination in our experimental CQDSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the calibration for spectral mismatch was conducted using a reference solar cell (Newport). Finally, following our previously reported method, LIC imaging of the CQDSCs was performed in a room‐temperature nitrogen environment under 10 Hz modulation frequency.…”
Section: Solar Cell Fabrication and Efficiency Optimizationmentioning
confidence: 99%
See 1 more Smart Citation